What It Is and Is Not: Pedagogy in Online Nursing Education Delivery - Lane, Annette M.; Stephens, Jennifer (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Nursing has employed distance education for decades. In the 21st century, distance programs have often been delivered online. This became even more prevalent since the COVID-19 pandemic. Despite the preponderance of online nursing courses, the delivery of courses virtually does not necessarily mean that these offerings are intentionally developed online education. We discuss a secondary analysis of data examining the formation of online nursing programs at Athabasca University. This historical inquiry used interpretive description of the pedagogy, both learning strategies and the theories that substantiate the strategies, using thematic analysis. Participants discussed their theoretical substantiation of online education. We posit that online nursing education involves a purposeful pedagogy including theoretical bases and would benefit from a strong sense of mission behind the course delivery. Findings from this study may apply to online programs, irrespective of profession or discipline.